Heterogeneity of Liver Disease in Common Variable Immunodeficiency Disorders - Pecoraro, Antonio; Crescenzi, Ludovica; Varricchi, Gilda; Marone, Giancarlo; Spadaro, Giuseppe (Frontiers in Immunology, 2020)
Common variable immunodeficiency (CVID) is the most frequent primary immunodeficiency (PID) in adulthood and ischaracterized by severe reduction of immunoglobulin serum levels and impaired antibody production in response to vaccines and pathogens. Beyond the susceptibility to infections, CVIDencompasses a wide spectrum of clinical manifestations related to a complex immune dysregulationthat also affects liver.Although about 50% CVID patientspresent persistently deranged liver function, burden andnature of liver involvement have not been systematically investigated in most cohort studies published in the last decades. Therefore, the prevalence of liver disease in CVID widely varies depending on the study design and the sampling criteria.This review seeks to summarize the evidence about the most relevant causes of liver involvement in CVID, including nodular regenerative hyperplasia, infections and malignancies. We also describe the clinical features of liver disease in some monogenic forms of PID included in the clinical spectrum of CVIDas ICOS, NFKB1, NFKB2, CTLA-4, PI3Kδ pathway, ADA2 and IL21-R genetic defects. Finally, we discuss the clinical applications of thevarious diagnostic toolsand the possible therapeutic approaches for the management of liver involvement in the context of CVID.